DeSoftIn: A methodological proposal for individual software development - González-Sanabria, Juan Sebastián; Morente-Molinera, Juan Antonio; Castro-Romero, Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Different Computer Engineering undergraduate programs over the world are demanding the students to present individual works and, particularly, to present a degree project, which in most cases is related to software development. However, when planning the projects, students find themselves with the problem of choosing a method to develop the software, since existent methods involve team work, but the degree project is supposed to be done individually, in order to evaluate the student’s acquired knowledge. This difficulty leads to projects that fail either to achieve the proposed objectives or to finish on the expected time, among other difficulties. This paper presents a methodological proposal for the development of individual software projects, mainly in academia, named "DeSoftIn", which will contribute to accomplish the project objectives, and will allow the students to approach development methodologies since the beginning of their studies.